HS-173 as a novel inducer of RIP3-dependent necroptosis in lung cancer. (1st March 2019) - Park, Jung Hee; Jung, Kyung Hee; Kim, Soo Jung; Yoon, Young-Chan; Yan, Hong Hua; Fang, Zhenghuan; Lee, Ji Eun; Lim, Joo Han; Mah, Shinmee; Hong, Sungwoo; Kim, You-Sun; Hong, Soon-Sun
Abstract: Necroptosis is a form of regulated necrotic cell death mediated by receptor-interacting kinase 3 (RIP3). Recently, necroptosis has gained attention as a novel alternative therapy to target cancer cells. In this study, we screened several chemotherapeutics used in preclinical and clinical studies, and identified a drug HS-173 that induces RIP3-mediated necroptosis. HS-173 decreased the cell survival in a dose-dependent manner in RIP3-expressing lung cancer cells, compared to the cells lacking RIP3. Also, the cell death induced by HS-173 was rescued by specific necroptosis inhibitors such as necrostatin-1 and dabrafenib. Additionally, HS-173 increased the phosphorylation of RIP3 and MLKL, which was decreased by necroptosis inhibitors, indicating that HS-173 activates RIP3/MLKL signaling in lung cancer cells. HS-173 increased the necroptotic events, as observed by the increased levels of HMGB1 and necroptotic morphological features. Furthermore, HS-173 inhibited the tumor growth by stimulation of necroptosis in mouse xenograft models. Our findings offer new insights into the role of HS-173 in inducing necroptosis by enhancing RIP3 expression and activating the RIP3/MLKL signaling pathway in lung cancer cells. Highlights: Necroptosis is a novel alternative therapy to target cancer cells. HS-173 induced necroptosis in lung cancer cells by enhancing the expression of RIP3 and activating RIP3/MLKL signaling pathway. The necroptotic events induced by HS-173 has been observed by the increased levels of HMGB1 and necroptotic morphological features. HS-173 inhibited the tumor growth by stimulation of necroptosis in mouse xenograft models. Our findings offer new insights into the role of HS-173 on inducing necroptosis through RIP3 activation in lung cancer cells.